Latrine Quality Associated with Diarrhoea Incidence in Mekarsari Health Centre Area, Lebak Regency - Sutomo, Omo; Rokayah, Yayah; Wasludin, Wasludin (Poltekkes Kemenkes Palu, 2024)
The World Health Organization defines sanitation as the provision of facilities and services for the disposal of human excreta, such as urine and feces, including family latrines. In 2019, the percentage of families in Banten province using latrines was 70.5%, lower than the national average of 72.3% for those using permanent sanitary latrines. Sanitation is related to environmental health, which influences public health. Poor sanitation conditions have negative impacts on various aspects of life, ranging from the degradation of community environmental quality to the contamination of drinking water sources, the increase in diarrheal diseases, and the emergence of other illnesses. Diarrheal diseases are potential endemic diseases with outbreaks often resulting in fatalities in Indonesia. The prevalence of diarrhea in 2018, diagnosed by healthcare professionals, was 6.8%, and based on self-reported symptoms, it was 8%. This study aims to determine the relationship between the quality of family latrines and the occurrence of diarrhea in the Mekarsari Community Health Center area, Lebak Regency, using a cross-sectional study design. The study population consists of all families with family latrines (goose-neck latrines) in the Mekarsari Community Health Center area, with a sample size of 88 families. Statistical chi-square tests were conducted at an alpha level of 0.05. The results indicate that nearly all respondents (93.2%) were male, predominantly in the productive age group (96.6%). The majority of respondents had low levels of education (67%), and almost all were non-civil servants (97.7%). Monthly income for most respondents (73.9%) was below the Lebak Regency Minimum Wage (< Rp 2,944,665). A proportion (17%) of families still had low-quality latrines, and some family members suffered from diarrhea (13.6%). There is a significant association between latrine quality and the occurrence of diarrhea (p=0.005). Families with low-quality latrines are over seven times more likely to suffer from diarrhea compared to those with high-quality latrines (OR=7.44). Empowerment through health education and support is necessary to enable families to understand, accept, and adopt behaviors to improve, construct, and maintain family latrines, thus ensuring diarrhea-free households.